2019
DOI: 10.4314/mmj.v31i4.4
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative cross-sectional survey of psychosocial stimulation and counselling interventions at nutritional rehabilitation units in Southern Malawi

Abstract: BackgroundInpatient treatment at nutritional rehabilitation units (NRUs) is needed for children who have severe acute malnutrition (SAM) and acute illness, loss of appetite, or severe oedema. World Health Organization guidelines state that nutritional counselling should be done with primary caregivers at NRUs. These recommendations also include psychosocial stimulation interventions to improve developmental outcomes in children with SAM. However, there is limited information about the delivery of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The results show that the developmental status as measured using the malnourished children's body mass indices were found to be significant compared to their baseline body mass index obtained. The finding, therefore, corroborates that of Allison et al (2019) and the World Health Organization guidelines which recommended psychosocial stimulation intervention as well as other supporting activities such as nutrition to improve developmental outcomes in children with malnutrition. Similarly, the study of Abesa et al (2019), where the researchers established that play-based psychomotor/psychosocial stimulation on the severe acute malnourished children shows a significant improvement on gross motor functions when combined with standard nutrient rich diet.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The results show that the developmental status as measured using the malnourished children's body mass indices were found to be significant compared to their baseline body mass index obtained. The finding, therefore, corroborates that of Allison et al (2019) and the World Health Organization guidelines which recommended psychosocial stimulation intervention as well as other supporting activities such as nutrition to improve developmental outcomes in children with malnutrition. Similarly, the study of Abesa et al (2019), where the researchers established that play-based psychomotor/psychosocial stimulation on the severe acute malnourished children shows a significant improvement on gross motor functions when combined with standard nutrient rich diet.…”
Section: Discussionsupporting
confidence: 85%
“…Several systematic review evidence indicated that integrating psychosocial intervention to nutritional interventions have resulted in positive cognitive and social-emotional benefits over nutritional intervention alone. A study conducted in Malawi in 2019 shows a comprehensive intervention was used to improve developmental and nutritional outcomes of the vulnerable children (Allison et al, 2019). Similarly, in a study conducted in University Specialized Hospital, Ethiopia, on the effects of play-based psychomotor/psychosocial stimulation on the severe acute malnourished children shows that the intervention group improved significantly on gross motor functions when combined with standard nutrient rich diet during hospital follow-up and on fine motor functions during the home follow-up.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors suggested post-training support for healthcare workers at NRUs, integration with emergency care in alignment with Emergency Triage Assessment and Treatment (ETAT), and pre-service training of healthcare workers which started in Malawi in 2016 (Kauchali et al, 2022). With fewer children admitted to NRUs meaning that many are not at capacity (Daniel et al, 2019; Kouam, 2016) – and many sitting empty – there is strong potential for this to be done without greatly increasing resource requirements.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of inappropriate water facilities, hand washing, and hygiene practices results in poor nutrition and health outcomes in children (Joshi & Amadi, 2013). A recently published systematic review clearly outlines the benefits of the provision of psychosocial stimulation for improve developmental and nutritional outcomes in children hospitalized with SAM in Jamaica and Bangladesh who received this type of intervention (Daniel et al, 2019;Daniel et al, 2017;Kerac et al, 2010;Grantham-McGregor et al, 1994). Several research reports show that the promotion and support of responsive caregiving can promote better nutritional status and development in children (Aboud et al, 2018;WHO, 2018;Engle et al, 2007;Daelmans et al, 2015).…”
mentioning
confidence: 99%